2018
DOI: 10.1002/slct.201800407
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on the Absorption Mechanisms of SO2 by Ionic Liquids

Abstract: A density functional theory study was conducted to explore the absorption mechanisms of SO2 by ionic liquids (ILs), including task specific ILs 1,1,3,3‐tetramethylguanidinium lactate ([TMG][LAC]), and normal ILs 1‐butyl‐3‐methylimidazolium tetrafluoroborate ([BMIM][BF4]) and 1‐butyl‐3‐methylimidazolium hexafluorophosphate ([BMIM][PF6]). The strength of chemical absorption by [TMG][LAC] is stronger than physical absorption, and the physical absorption energy follows the order of [TMG][LAC] > [BMIM][BF4] > [BMIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In [ 38 ], it has been shown how aqueous solutions of AAILs are efficient absorbent media and how SO 2 can be regenerated after absorption by heating at 100 °C. In [ 39 ], a guanidium-based IL has been shown to undergo chemical reaction by means of its NH 2 group to yield an –NH–SO 2 structure.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 38 ], it has been shown how aqueous solutions of AAILs are efficient absorbent media and how SO 2 can be regenerated after absorption by heating at 100 °C. In [ 39 ], a guanidium-based IL has been shown to undergo chemical reaction by means of its NH 2 group to yield an –NH–SO 2 structure.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research on SO 2 absorption using [TMG]­[Lac] IL found that the high SO 2 absorption capacity was due to both physical and chemical absorption. [TMG]­[Lac] results showed that 1 mol of [TMG]­[Lac] absorbed one mol of SO 2 from a mixture of SO 2 and N 2 at 40 °C under ambient pressure. ,, Guanidinium-based ILs were synthesized by Shang et al. and demonstrated to be excellent SO 2 absorbers .…”
Section: Introductionmentioning
confidence: 99%
“…16,28,29 Guanidinium-based ILs were synthesized by Shang et al and demonstrated to be excellent SO 2 absorbers.…”
mentioning
confidence: 99%